THERMAL PERFORMANCE AND ENVIRONMENTAL IMPACT OF CONTEMPORARY EARTH ARCHITECTURE IN PORTUGAL - Macedo, Célia; Chandiwala, Smita (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
Guaranteeing protection against the climatic elements no longer represents the single purpose of a building. Thermal comfort and well-being of its occupants has become increasingly important as living standards of modern societies have risen considerably, mostly made possible by a constant and inexpensive supply of energy from fossil fuels. This energy used to heat and cool our buildings, is now recognised as a major contributing factor for climate change, caused by greenhouse gas emissions in the environment. There is hence, an urgent need to move towards environmentally sustainable buildings which maintain comfort while reducing their dependence on fossil fuels, to minimise and counter this threat posed by climate change. Earth, represents a low environmental impact building material and has been used for centuries, in traditional and vernacular architecture to provide comfort by responding to local climatic conditions. Revisiting those techniques and applying current knowledge and skills to earth architecture, has the potential to contribute towards reducing the environmental impact of present day buildings while still maintaining comfortable conditions for the occupants. Previous research has mostly studied the technical aspects of earth construction, with limited focus on thermal performance of earth buildings and especially, its relation to the thermal comfort of the occupants. Within this context, this study tests the viability of employing earth construction in low rise dwellings with a particular emphasis on its thermal performance. This paper reflects the study carried out within the framework of an MSc thesis, on the analyses of the thermal performance of contemporary earth houses, focusing on three case studies located in the southern area of Alentejo in Portugal. The methodology used combines thermal modelling of the houses with real data collection of internal temperatures during both the summer and the winter periods. It is accompanied with occupant surveys to assess the users’ perception of internal conditions within the house. The study hence focuses on both the ‘hard’ quantifiable data and the less identifiable but equally important ‘soft’ qualitative information from the surveys, to holistically evaluate the role of earth construction in achieving thermal comfort in contemporary dwellings in Portugal as well as its possible contribution towards a more sustainable future. The findings from this research work led to the conclusion that rammed earth, when used with no insulation, although it shows a very effective thermal behaviour during the summer fails to provide comfortable thermal conditions during the coldest periods of the year. However, this problem can be overcome when insulation is used, thus providing thermal comfort both during the winter and during the summer.